Dyspnea as an Unusual Presentation of Rickets in A 3-Month-Old Infant: A Case Report - Okudo, Jerome (Journal of Diagnostics, 2016)
Rickets, a condition caused by a deficiency of vitamin D, has a myriad of presentations and affects children all over the world. Infants who are exclusively breastfed by mothers who are vitamin D deficient are affected, particularly in the absence of vitamin D supplementation during pregnancy. While breast feeding is encouraged, breast milk is deficient in vitamin D thus; exclusively breastfed infants require vitamin D supplementation. This case describes a three-week-old male infant with a continuum of rickets, which went undiagnosed from the initial presentation of noisy, difficult breathing and snoring at the pediatric emergency department. This case emphasizes that rickets may not always have a classical presentation.